Perampanel as a treatment option for orthostatic tremor. (September 2022) - van der Woude, E.V.; Babeliowsky, W.A.; de Bie, R.M.A.; van Rootselaar, A.F.
Highlights: Perampanel is a new therapeutic option for orthostatic tremor. Perampanel improves daily functioning and health perception. Tolerance for perampanel is low compared to standard medication.